Predatory functional responses under increasing temperatures of two life stages of an invasive gecko - Haubrock, Phillip J; Cuthbert, Ross N; Veselý, Lukáš; Balzani, Paride; Baker, Nathan Jay; Dick, Jaimie T A; Kouba, Antonín (Scientific reports, 2020)
The direct effects of temperature increases and differences among life-history might affect the impacts of native and invasive predators on recipient communities. Comparisons of functional responses can improve our understanding of underlying processes involved in altering species interaction strengths and may predict the effect of species invading new communities. Therefore, we investigated the functional responses of the mourning gecko Lepidodactylus lugubris (Duméril & Bibron, 1836) to explore how temperature, body-size and prey density alter gecko predatory impacts in ecosystems. We quantified the functional responses of juvenile and adult geckos in single-predator experiments at 20, 23 and 26 °C. Both displayed saturating Type-II functional responses, but juvenile functional responses and the novel Functional Response Ratio were positively affected by temperature as juvenile attack rates (a) increased as a function of increased temperature. Handling times (h) tended to shorten at higher temperature for both predator stages. We demonstrate that the effects of temperature on functional responses of geckos differ across ontogeny, perhaps reflecting life-history stages prioritising growth and maturation or body maintenance. This indicates that temperature-dependent gecko predatory impacts will be mediated by population demographics. We advocate further comparisons of functional responses to understand the invasiveness and future predatory impacts of geckos, and other invasive species globally, as temperatures change.
Keywords: Behavior, Animal; Lizards; ekosystém; Predatory Behavior; ještěři; zavlečené druhy; potravní řetězec; věkové faktory; predátorské chování; zvířata; Temperature; populační dynamika; Introduced Species; Food Chain; chování zvířat; Age Factors; Population Dynamics; Ecosystem; teplota; Animals